If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3z + -6 = -6z + -15 Reorder the terms: -6 + 3z = -6z + -15 Reorder the terms: -6 + 3z = -15 + -6z Solving -6 + 3z = -15 + -6z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '6z' to each side of the equation. -6 + 3z + 6z = -15 + -6z + 6z Combine like terms: 3z + 6z = 9z -6 + 9z = -15 + -6z + 6z Combine like terms: -6z + 6z = 0 -6 + 9z = -15 + 0 -6 + 9z = -15 Add '6' to each side of the equation. -6 + 6 + 9z = -15 + 6 Combine like terms: -6 + 6 = 0 0 + 9z = -15 + 6 9z = -15 + 6 Combine like terms: -15 + 6 = -9 9z = -9 Divide each side by '9'. z = -1 Simplifying z = -1
| 6x^3-21x^2-12x=0 | | -3(8p+6)-2(6-17p)=3(2+3p) | | 3x^2+7x+30=0 | | -0.9x+8.19=-0.7x+4.79 | | (3/11)z=-5 | | lnx-2ln=ln^4 | | 4(m-3)=8m-40 | | 10=x+5-2x | | y-10=37 | | 14y^2=18 | | 7y+9+3y+9=143 | | a+17=-19 | | -4.5a=-32.4 | | -(5/9)k=2 | | x+56=x-23 | | 7x+9=4x+12 | | a+19=-17 | | (10t-5t+14)+(11t-8)= | | 5y+14-8y=-20 | | 7w-4w-3=12 | | 0.7x-0.3x+5=7 | | 3x=450 | | 84=20x | | 3x+4x-8=2(2x+5) | | 2x=8x+2 | | 3y^2-16y+20=0 | | -12=-6x+2(x-4) | | -9z=9 | | 3.2=1.4+x | | 3x-8=2x+17 | | -v+2v+6=-3 | | 24x+18y= |